Protein Phylogenetic Analysis of Ca2+/cation Antiporters and Insights into their Evolution in Plants - Emery, Laura; Whelan, Simon; Hirschi, Kendal D.; Pittman, Jon K. (Frontiers in Plant Science, 2012)
Cation transport is a critical process in all organisms and is essential for mineral nutrition, ion stress tolerance, and signal transduction. Transporters that are members of the Ca2+/Cation Antiporter (CaCA) superfamily are involved in the transport of Ca2+ and/or other cations using the counter exchange of another ion such as H+ or Na+. The CaCA superfamily has been previously divided into five transporter families: the YRBG, NCX, NCKX, CAX and CCX families, which include the well-characterized Na+/Ca2+ exchanger (NCX) and H+/cation exchanger (CAX) transporters. To examine the evolution of CaCA transporters within higher plants and the green plant lineage, CaCA genes were identified from the genomes of sequenced flowering plants, a bryophyte, lycophyte, and freshwater and marine algae, and compared with those from non-plant species. We found evidence of the expansion and increased diversity of flowering plant genes within the CAX and CCX families. Genes related to the NCX family are present in land plant though they encode distinct MHX homologs which probably have an altered transport function. In contrast, the NCX and NCKX genes which are absent in land plants have been retained in many species of algae, especially the marine algae, indicating that these organisms may share ‘animal-like’ characteristics of Ca2+ homeostasis and signaling. A group of genes encoding novel CAX-like proteins containing an EF hand domain were identified from plants and selected algae but appeared to be lacking in any other species. Lack of functional data for most of the CaCA proteins make it impossible to reliably predict substrate specificity and function for many of the groups or individual proteins. The abundance and diversity of CaCA genes throughout all branches of life indicates the importance of this class of cation transporter, and that many transporters with novel functions are waiting to be discovered.